Optical electroosmotic magnetic density with antiferromagnetic model - Korpinar, Talat; Korpinar, Zeliha; Yeneroglu, Mustafa (Springer, 2023)
In our manuscript, we obtain optical angular momentum of phi(alpha), phi(t), phi(s) by using optical spherical frame. Also, we construct magnitude of optical angular momentum and spherical magnetic moment of phi(alpha), phi(t), phi(s). Thus, we illustrate optical tau(phi(alpha)), tau(phi(t)), tau(phi(s)) magnetic torque phase microscale. Moreover, we have electroosmotic microfluidic tau(phi(alpha)), tau(phi(t)), tau(phi(s)) magnetic torque density. Finally, we design electroosmotic magnetic torque density with antiferromagnetic model.
Keywords: Optical angular momentum; Spherical magnetic moment; Magnetic torque density; Torque phase